2017
DOI: 10.9767/bcrec.12.2.775.227-234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weight Hourly Space Velocity and Catalyst Diameter on Performance of Hybrid Catalytic-Plasma Reactor for Biodiesel Synthesis over Sulphated Zinc Oxide Acid Catalyst

Abstract: Biodiesel synthesis through transesterification of soybean oil with methanol on hybrid catalytic-plasma reactor over sulphated zinc oxide (SO4 2-/ZnO) active acid catalyst was investigated. This research was aimed to study effects of Weight Hourly Space Velocity (WHSV) and the catalyst diameter on performance of the hybrid catalytic-plasma reactor for biodiesel synthesis. The amount (20.2 g) of active sulphated zinc oxide solid acid catalysts was loaded into discharge zone of the reactor. The WHSV and the cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Biofuels, such as biodiesel (FAME, fatty acid methyl ester), green gasoline (bio-gasoline), green kerosene, and green diesel (fossil diesel-like), can be produced from vegetable oils. Biodiesel production from vegetable oils was widely studied by researchers, in which the most developed process of biodiesel production was transesterification. However, biodiesel needs to be mixed with fossil diesel, and its hygroscopicity caused the clogging in the engine filter . Furthermore, the engine needs to be modified for the use in mixtures with fossil diesel at levels above 20% .…”
Section: Introductionmentioning
confidence: 99%
“…Biofuels, such as biodiesel (FAME, fatty acid methyl ester), green gasoline (bio-gasoline), green kerosene, and green diesel (fossil diesel-like), can be produced from vegetable oils. Biodiesel production from vegetable oils was widely studied by researchers, in which the most developed process of biodiesel production was transesterification. However, biodiesel needs to be mixed with fossil diesel, and its hygroscopicity caused the clogging in the engine filter . Furthermore, the engine needs to be modified for the use in mixtures with fossil diesel at levels above 20% .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, 3.0% catalyst loading can be considered the optimum loading level in this process. It was also reported by Buchori et al 55 that with increasing the amount of catalyst, the available surface area accessible on the catalyst relative to the total volume of the reaction medium would increase. As a result, more basic sites are available for the catalytic reaction, increasing the reaction rate between the adsorbed reactant molecules and the reactive species.…”
Section: Resultsmentioning
confidence: 65%
“…As expected, it has been observed that the yield of biodiesel increases when the weight percent of the catalyst increases. This is due to the increase of the available surface area of the catalyst per unit volume of the reaction media, and hence, the increase of the basic sites required for the catalytic reaction [24]. Figure 8 shows the effect of the reaction temperature on the yield of biodiesel.…”
Section: The Effect Of Amount Of Catalystmentioning
confidence: 99%